Severe allergic reactions at a tertiary paediatric service 2014 - 2016 - Chippendale, Sa-Eeda (Department of Paediatrics and Child Health, 2019)
Introduction: Anaphylaxis is a severe, life-threatening generalized hypersensitivity reaction. The European Anaphylaxis Registry was established to review and improve medical management of these patients, facilitate accurate comparisons between centres, highlight public health implications, and examine trends in treatment over time. This is replicated here in a South African setting. Methods: Participants comprised patients treated at Red Cross War Memorial Children’s Hospital (RCWMCH) for severe allergic reactions between January 2014 and August 2016. Recruitment was by applying relevant ICD- 10 coding to the hospital’s clinical summary system of admissions and discharges, the pharmacy’s records of adrenaline autoinjector dispensing, and referrals from the allergy department’s clinical staff. Participants who were screened but did not meet inclusion criteria after preliminary questioning and/or folder review were excluded. 156 episodes were analyzed. A local web-based registry was established, and used to capture data collected via a questionnaire in interviews at the RCWMCH Allergy Clinic. Results: Males, younger children, and participants of coloured ethnicity were more frequently affected. Skin and mucosa was most commonly involved, followed by respiratory and gastrointestinal upset, with cardiovascular and other systemic involvement occurring infrequently. More than 40% of episodes were graded as severe. Specific IgE was the most frequently requested testing. Nearly two-thirds of patients were seen with a recurrent episode. Food-related triggers predominated and decreased with age: particularly peanut, hen’s egg, fish, cashew nuts and cows’ milk. There was a strong correlation with atopic conditions, in excess of international trends. 3 Adrenaline was rarely used, by both lay persons when previously prescribed, and by professional attenders. Hospital admissions were infrequent, and no deaths were recorded. Prophylactic measures were almost universally instituted, but the success thereof could be improved. Conclusion: This is the first local comprehensive description of anaphylactic trends. Further areas of research are suggested: to investigate the propensity for allergic reactions in the coloured population, our much higher rate of association with other atopic disorders compared to international patterns, comparison of our baseline comorbid conditions for contextual analysis, and a review of barriers to care. Ongoing education and training to patients, parents, teachers, and health care workers is identified as a major area requiring intensification.